2016
DOI: 10.1007/s00405-016-4058-6
|View full text |Cite
|
Sign up to set email alerts
|

The possible mechanisms of the human microbiome in allergic diseases

Abstract: In the present paper, we discuss the importance of the microbiome in allergic disease. In this review paper, the data from the Medline (PubMed) and search engine of Kirikkale University were systematically searched for all relevant articles in June 15th, 2015 for the past 30 years. The keywords of "microbiome", "dysbiosis", "allergy", "allergic rhinitis", "allergic disease", "mechanisms" and "treatment" were used alone or together. In this paper, microbiomes were presented in terms of "Definition", "Influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 93 publications
1
78
0
2
Order By: Relevance
“…IECs act as a barrier between luminal microbiota and gutassociated immune cells. 30 In vitro, in vivo, and several intestinal epithelial cell lines express TLRs. 31 TLRs play a pivotal role in maintaining the gut homeostasis through secretion of pro-inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…IECs act as a barrier between luminal microbiota and gutassociated immune cells. 30 In vitro, in vivo, and several intestinal epithelial cell lines express TLRs. 31 TLRs play a pivotal role in maintaining the gut homeostasis through secretion of pro-inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…The early microbiota of children who later developed allergies has been characterised by lower bacterial diversity, with predominant Firmicutes , higher counts of the Bacteroidaceae , increased numbers of the anaerobic Bacteroides fragilis , Escherichia coli , Clostridium difficile , Bifidobacterium catenulatum , Bifidobacterium bifidum and Bifidobacterium longum. In contrast and decreased numbers of Bifidobacterium adolescentis , Bifidobacterium bifidum and Lactobacillus have been reported . When the microbiota of children with allergies was assessed at the onset of allergic symptoms in one study, it showed a different pattern, with higher counts of Bacteroides , lower counts of Akkermansia muciniphila, Faecalibacterium prausnitzii and Clostridium and overall lower bacterial diversity .…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanisms underlying an increased risk of sensitisation and allergy development, detected as a consequence of dysbiosis in animal models, have been related to various alterations in mucosal regulatory T cells. Other reported effects were defects in the epithelial barrier function, as evidenced by increased mucosal permeability, diminished secretory immunoglobulin A production and excretion and altered dendritic and B‐cell function .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has recently been suggested that imbalances in the composition of the intestinal microbiota might trigger allergy. The intestinal microbiota not only regulates the intestinal mucosal immune system but also takes part in systemic inflammatory responses [22]. It has been found that a reduced gut microbial diversity in infancy is associated with an increased risk of allergic manifestations in school-aged children [23].…”
Section: Discussionmentioning
confidence: 99%